Riak core - Sheehy, Justin; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, CA) ([United States?] : O'Reilly Media, 2011)
"Riak Core is a general implementation of a distributed systems model, enabling you to build a customized, scalable, highly available distributed system without too huge an investment. Justin will explain that model, its history, and how it can be used to build new data processing systems." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Electronic data processing; Database management -- Computer programs; Electronic books